Komunikasi Transbudaya Antara Pemulung Dengan Pengepul Dalam Mengais Rejeki Di Pagar Gunung Bandung - Agus Triyono; Sonef Riyadi (Faculty of Social and Political Science, Universitas Airlangga, 2015)
This study analyses trans-cultural communication between scavengers and collectors and their effort to generate income in Pagargunung, Bandung. Different characters lead them to perform trans-cultural communication, depend on their occupation background and cultur origin. Through Trans-cultural Communication process, they set agrreable price of junk that has gathered and collected by scavengers to be cashed at the mediator. This study aims to comprehend trans-cultural communication process between scavenger and collector. This research discussed svacengers and collectors’ role in performing their job. Both make a joint commitment in determining the outcomes of cultural differences in the process Trans-cultural Communication. This research method uses the basic research descriptive case study, aiming to understand and to describe in detail the condition trans-cultural communication phenomenon of scavengers and collectors. The results of this study concluded that there is trans-cultural communication between scavengers and collectors from various origin, even they have different culture, language, and role in their profession.